Atividades biológicas de uma fração polissacarídica sulfatada da alga marinha verde Caulerpa cupressoides var. lycopodium (Vahl) C. Agardh - Rodrigues, José Ariévilo (2011)
Seaweeds sulfated polysaccharides (SPs) are of interest biomedicinal. The aim of this study was to investigate the effects of a SP fraction from Caulerpa cupressoides (Chlorophyta) on coagulation, thrombosis, pain, inflammation and toxicity. Swiss mice (28-32 g) and Wistar rats (180-220 g) were used. Alga was submitted to three sequential extractions with papain and yielded 3.15, 1.11 and 0.35% of total SPs, respectively. The fractionations on DEAE-cellulose of the total SPs of the two first extractions resulted into three SP fractions (F 1-0.5 M, F 11-0.75 M and F III-1 M, respectively) that revealed by agarose gel electrophoresis differences in standard and charge density pattern, and from 8.72 to 23.79% of sulfate. The analysis by GPC of the SP fractions (first extraction) showed as heterogeneous systems (from 2.1 to 4.12 x 10 g moL ) and when analyzed by infrared consisting of ester sulfate, uronic acid and galactose-6- sulfate. Fraction F H suggested anticoagulant effect (24.6 IU mg ) possibly antithrombin-dependent (IC5o = ca. 10 mg mL'1). This fi'action, when tested in a model of venous thrombosis in rats, inhibited (p < 0.05) the formation of thrombus (29.87 ± 0.45% and 70.56 ± 0.37% for 1 and 2 mg kg'\ respectively) compared to control group, but at higher doses (> 2 mg kg-l) was hypercoagulability induced. F II (3, 9 or 27 mg kg-I, i. v.) reduced the number of abdominal constrictions (57, 89.9 and 90.6%, respectively), both phases of the formalin test (42.47 and 52.10% first-phase (9 and 27 mg kg'1, respectively), 68.95, 82.34 and 84.61% second-phase) and increased the latency time of mice (9 mg kg ) hot-plate test, compared to control groups (p < 0.05). F II (3, 9 or 27 mg kg ) decreased the total leukocytes (46, 49 and 53%) and neutrophils (64, 69 and 73%) migrations, respectively, as well as the rat paw edema induced by carrageenan not being different from the dexamethasone. Mice were tolerant to TSPs (9 mg kg , i.p.) administered for 14 consecutive days and no changes in liver or kidney were observed (p > 0.05). These findings were confirmed by histological analysis. Therefore, the fraction F II from C. ciipressoides shows to be safe and having anticoagulant, antithrombotic, pro-thrombotic, analgesic and anti-inflammatory actions.